Maigret: conocimiento por connaturalidad y conciencia concomitante - Noain Calabuig, Juan José (Revista de Filosofía, 2002)
The present article analyses, in its first part, recurrences of the personality of the commissioner Maigret, famous personage of fiction of the novelist Belgian Simenon. Subsequently it is tried to notify two apparent difficulties that present those recurrences: – on the one hand, the resolved negation of method on the part of the commissioner arranged with a behaviour investigator characteristic; – by another side, some results surprising at par that is supposed, during the development of the investigations, a permanent suspension of the thought. To resolve these contradictions apparently insoluble, will resort, in the last section, to two categories of knowledge elaborated by the philosophy: the already classical knowledge by connaturality; and the conscience concomitant or inobjective, lending special attention, in the referring thing to this modality of conscience, to the work of the Spanish philosopher Antonio Millán-Puelles.